Life - Lewis, Ricki (McGraw-Hill Higher Education, 2004)
Convey learning through independent discovery with the investigative experiments in this unique lab manual. Written in a fresh, engaging style, Life Laboratory Manual asks students to actively participate in setting up and preparing experiments rather than just using conventional, commercially available materials.